α-Glucan Phosphorylase MalP of Corynebacterium glutamicum Is Subject to Transcriptional Regulation and Competitive Inhibition by ADP-Glucose - Clermont, Lina; Macha, Arthur; Müller, Laura M; Derya, Sami M; von Zaluskowski, Philipp; Eck, Alexander; Eikmanns, Bernhard J; Seibold, Gerd M (Journal of bacteriology, 2015)
α-Glucan phosphorylases contribute to degradation of glycogen and maltodextrins formed in the course of maltose metabolism in bacteria. Accordingly, bacterial α-glucan phosphorylases are classified as either glycogen or maltodextrin phosphorylase, GlgP or MalP, respectively. GlgP and MalP enzymes follow the same catalytic mechanism, and thus their substrate spectra overlap; however, they differ in their regulation: GlgP genes are constitutively expressed and the enzymes are controlled on the activity level, whereas expression of MalP genes are transcriptionally controlled in response to the carbon source used for cultivation. We characterize here the modes of control of the α-glucan phosphorylase MalP of the Gram-positive Corynebacterium glutamicum . In accordance to the proposed function of the malP gene product as MalP, we found transcription of malP to be regulated in response to the carbon source. Moreover, malP transcription is shown to depend on the growth phase and to occur independently of the cell glycogen content. Surprisingly, we also found MalP activity to be tightly regulated competitively by the presence of ADP-glucose, an intermediate of glycogen synthesis. Since the latter is considered a typical feature of GlgPs, we propose that C. glutamicum MalP acts as both maltodextrin and glycogen phosphorylase and, based on these findings, we question the current system for classification of bacterial α-glucan phosphorylases. IMPORTANCE Bacterial α-glucan phosphorylases have been classified conferring to their purpose as either glycogen or maltodextrin phosphorylases. We found transcription of malP in C. glutamicum to be regulated in response to the carbon source, which is recognized as typical for maltodextrin phosphorylases. Surprisingly, we also found MalP activity to be tightly regulated competitively by the presence of ADP-glucose, an intermediate of glycogen synthesis. The latter is considered a typical feature of GlgPs. These findings, taken together, suggest that C. glutamicum MalP is the first α-glucan phosphorylase that does not fit into the current system for classification of bacterial α-glucan phosphorylases and exemplifies the complex mechanisms underlying the control of glycogen content and maltose metabolism in this model organism.